2021
DOI: 10.4143/crt.2020.847
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide, Population-Based Epidemiology Study of Primary Central Nervous System Tumors in Korea, 2007-2016: A Comparison with United States Data

Abstract: The purpose of this study was to determine the epidemiologic characteristics and survival of patients with primary brain and other central nervous system (CNS) tumors in Korea and to compare our findings with those from the United States. Materials and Methods We collected data on primary brain and CNS tumors diagnosed between 2007 and 2016 from the Korea Central Cancer Registry. The age-standardized incidence rates (ASRs) and 5-year relative survival rates (RSRs) were evaluated. We applied the classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Further studies in White populations also support a male prepondance 1 , 19 , 32 , 35 37 , 45 . In the Korean population, the IRRs (male-female ratio) were 1.31, 1.32, 1.27, 1.36 18 , 31 , 41 , 46 . Four studies based on Chinese have reported IRRs of 1.57, 1.69, 1.43, and 1.34 ( Figure 2B ) 19 , 38 , 39 , 47 .…”
Section: Epidemiology Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies in White populations also support a male prepondance 1 , 19 , 32 , 35 37 , 45 . In the Korean population, the IRRs (male-female ratio) were 1.31, 1.32, 1.27, 1.36 18 , 31 , 41 , 46 . Four studies based on Chinese have reported IRRs of 1.57, 1.69, 1.43, and 1.34 ( Figure 2B ) 19 , 38 , 39 , 47 .…”
Section: Epidemiology Characterizationmentioning
confidence: 99%
“…In Japan, the ASR was 1.26 in Miyazaki prefecture 30 . Four Korean studies reported ASR values of 0.59, 0.77, 0.87, and 1.11 ( Figure 2A ) 18 , 31 , 41 , 42 . Lower ASR in East Asians was still observed when only older adults (≥40 years of age) were considered 18 .…”
Section: Epidemiology Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mongolia the most common location of CNS tumours was the brain regardless of sex and age. In contrast, the meninges were the most common location in other large registries such as Korea and the United States of America (US) [17,18]. However, those registries collect data on non-malignant tumours and the meningeal tumours were most likely non-malignant.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 308,102 new cases and 251,329 brain and CNS tumor deaths were diagnosed globally in 2020 (2). The incidence of brain and central nervous system tumors has increased in several regions since the standardization of tumor registration and the improvement of diagnostic techniques (4,7,8).…”
Section: Introductionmentioning
confidence: 99%